Cyber space bullying - Popović-Ćitić Branislava (Temida)
Cyber space bullying is a relatively new phenomenon that has received increased attention by scientists, researchers and practitioners in recent years. It is usually defined as an intentionally and repeatedly expression of aggression towards other people through information and communication technologies. Cyber space bullying is characterized by all the primary characteristics of traditional bullying and some specifics ones that clearly differ it from other forms of bullying. In addition to the analysis of characteristics and specifics of cyber space bullying, the paper describes the basic forms of cyber space bullying (flaming, harassment, denigration, impersonation, outing, trickery, exclusion, stalking and happy slapping), as well as, the types of cyber space bullies (vengeful angel, power-hungry, revenge of the nerd, mean girls and inadvertent). The main goal of this paper is to provide initial theoretical guidelines for designing future empirical research on the complex phenomenon of cyber space bullying.